Air pollution and cultural heritage : proceedings of the International Workshop on Air Pollution and Cultural Heritage, 1-3 December 2003, Seville, Spain /: proceedings of the International Workshop on Air Pollution and Cultural Heritage, 1-3 December 2003, Seville, Spain. (©2004) - Unknown
No abstract available